PENGARUH OPINI AUDIT, PERGANTIAN AUDITOR DAN LABA/RUGI PERUSAHAAN TERHADAP AUDIT DELAY (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2019-2021) - Hidayah, Nurul; Muntiah, Nur Sayidatul; Hartono, Arif (JURNAL ILMIAH EDUNOMIKA, 2025)
Public companies have the obligation to submit financial reports to OJK on time. Delay in submitting financial reports is called audit delay. There are still several companies that are late in submitting their financial reports to the OJK. This research aims to test empirically the effect of audit opinion, auditor turnover and company profits/losses on audit delay partially and simultaneously. The population in this study were all property and real estate sector companies listed on the IDX as many as 81 companies. The sampling technique in this study was purposive sampling, namely sampling based on criteria. The criteria used are companies that reported their finances consecutively on the IDX during 2019-2021. The type of data used is secondary data with data collection using the documentation method. The data used is the financial statements of property and real estate companies for 2019-2021. The data analysis method used is logistic regression analysis, and hypothesis testing using the help of variables with the SPSS application. The results of the study show that the first hypothesis is rejected, meaning that audit opinion has no effect on audit delay. Hypothesis 2 is rejected indicating that auditor change has no effect on audit delay. Hypothesis 3 is accepted, meaning that the company's profit or loss affects the occurrence of audit delay. The fourth hypothesis is accepted, meaning that simultaneously the variables of audit opinion, auditor turnover and company profits/losses affect audit delay.